“The Old Village”: Yup’ik Precontact Archaeology and Community-Based Research at the Nunalleq Site, Quinhagak, Alaska - Knecht, Rick; Jones, Warren (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2019)
Centred on the underresearched precontact archaeology of southwest coastal Alaska, the Nunalleq project is a decade-long collaboration between the Yup’ik village of Quinhagak and the University of Aberdeen. The Nunalleq archaeological site, like countless others in the Arctic, is being rapidly destroyed by the combined effects of global warming. Newly thawed permafrost soils are extremely vulnerable to rapid marine erosion from rising sea levels and decreases in seasonal ocean ice cover. Organic artifacts at the site have been preserved in remarkably intact condition, revealing an extraordinary record of precontact Yup’ik culture. But with the disappearing permafrost, this archaeological and ecological record is gradually decomposing, and recovery and analysis has become time critical. The Nunalleq project is a community-based response to locally identified needs to both recover threatened archaeological heritage and to find new ways to reconnect young people to Yup’ik culture and tradition. The results of the project have far exceeded our original expectations. Similar collaborative efforts may be the best hope for addressing threatened archaeological heritage in the North and beyond.